PENGARUH KONSELING GIZI TERHADAP PENGETAHUAN HIPERTENSI DAN SISA MAKANAN PASIEN HIPERTENSIDI RSUD DR R SOETIJONO BLORA - Hetty Dwi Kusumaningrum; Ana Yuliah Rahmawati; Wiwik Wijaningsih (Poltekkes Kemenkes Semarang, 2016)
Background :Food waste of hypertensive patients in DR R SoetijonoBlora hospital in December 2015 by 32.6 % , which means above the minimum service standards specified nutritional services . Nutritional counseling is done is a means to inform and motivate the patient so that the expected impact on increasing the patient's intake of food and less food waste . Objective :Knowing the influence of nutrition counseling on knowledge of hypertension and the food waste of hypertensive patients in DR R SoetijonoBlorahospital. Methods :This type of research is pre Experiment with one group pretest and posttest design . Sampling was done by using consecutive sampling as many as 35 people hospitalized hypertensive patients according to criteria of inclusion .Foodwaste is obtained by Comstock visual method , whereas knowledge of hypertension were taken using a questionnaire. Nutritional counseling is done two times in 2 days. Data taken with 3 times the measurement and analyzed used Friedman Test . Results: This study shows that there is influence nutritional counseling to the knowledge of hypertension ( p = 0.000 ) and there is influence nutritional counseling to food waste( p = 0.000 ). Conclusion :Nutritional counseling influencing knowledge about hypertension and food waste of hypertensive patients .